STUDI DESKRIPSI PENGETAHUAN IBU TENTANG INFEKSI CACING PADA BALITA DI DESA KARANGENDEP PATIKRAJA BANYUMAS - Trisnawati, Yuli (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2017)
Currently infectious diseases are still a major health problem in the world, especially in tropical countries. Among the infectious diseases, it turns out to date Parasitic diseases seem to get less attention from the community. According to WHO, Soil-Transmitted Helminth is one of the most common infectious diseases in many parts of the world, and usually concerns low-income groups. This infection is transmitted through oral fecal, where the eggs of the worms contaminate the soil around the poor sanitary dwellings. The purpose of this study is to determine the level of knowledge of the mother about the infection of worms in infants. The research method used is descriptive research with accidental sampling. The result is 59%, the knowledge level of infant mother about the infant worm infection is enough, 94% of respondents have been able to answer correctly about the understanding of worm infections in toddlers, 65% of respondents are still wrong in answering about the signs and symptoms of worm infections in infants, 76% of respondents were able to answer correctly about the cause of worm infections in toddlers, 88% of respondents have been able to answer correctly about infectious helminth infections in toddlers, 88% of respondents have been able to answer correctly about complications of infections of worms in infants and 53% of respondents are still wrong in answering about prevention of worm infections in infants. Keywords: knowledge of worm infection